On the influence of local deflections on the stability and the postbuckling behavior of composite cylindrical shells under external pressure - Semenyuk, N.P.; Zhukova, N.B.; Ivanova, N.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
The method of calculation of the stability and the postbuckling behavior of composite cylindrical shells with local imperfections under external pressure is offered. At its development, the equations of the Timoshenko—Mindlin theory of shells, the relations of the asymptotic method by Byskov—Hutchinson, and the method of a continuous prolongation for the solution of non-linear algebraic equations are used. The local imperfections are approximated by trigonometric Fourier series. At the determination of critical loads and the trajectory of deformation, the number of interacting modes, which is sufficient for deriving the result of a necessary accuracy, is found.